Assessing the Environmental Impact of the Intensification of Agricultural Production - VORONKOVA, Olga; SYCHEVA, Irina; KOVALEVA, Irina; KHASANOVA, Alfiia; GOROVOY, Sergey; VOROZHEYKINA, Tatiana (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
The article presents the results and consequences of the intensification of agricultural production over the past decades. The aim of the study is to assess the environmental consequences of the intensification of agricultural production, as well as the land and agrarian reforms, in particular, the consequences of the development of virgin and fallow lands. The article presents the emerged dilemma of further development of agricultural production and preservation of the natural environment as the basis for the life of future generations, which predetermined the search for alternative development options for the industry. At the present stage of development of agricultural production, one of the main tasks is to optimize the use of land resources and to choose methods that ensure the stability of functioning of agricultural landscapes in accordance with their natural properties. The fallow land area for agricultural use in Russia is more than 30 million hectares. This concerns, first of all, arable land, subject to wind and water erosion, left to be used as fallow land in difficult socio-economic conditions during the years of reform.